The Synergy of Influencer Marketing, Interactive Content, and Digital Strategies in Enhancing Visibility and Sales of MSME Products During Ramadan - Azzaakiyyah, Hizbul Khootimah; Suherlan; Rijal, Syamsu (Technology and Society Perspectives (TACIT), 2025)
This study examines the synergy between influencer marketing, interactive content, and digital strategies in increasing the visibility and sales of MSME products during Ramadan. Using a literature review method and a qualitative approach, this study analyzes 21 selected articles from Google Scholar and other credible sources published between 2021 and 2025. The findings reveal that influencer marketing plays a crucial role in building consumer trust and expanding market reach, particularly through collaborations with micro-influencers who have strong engagement with their audience. Interactive content, such as live shopping and social media challenges, has been proven to enhance customer engagement and strengthen brand loyalty. Additionally, the implementation of digital strategies, including paid advertising and consumer behavior analysis, enables MSMEs to effectively target their audience and increase sales conversion. Case studies of MSMEs such as Jiniso Indonesia, Mamahke Jogja, and Azarine Beauty demonstrate that the combination of these three strategies can lead to significant sales growth during Ramadan. However, challenges in implementing these strategies persist, including budget constraints, changes in social media algorithms, and difficulties in maintaining content consistency.